Trade openness, capital inflows and financial development in developing economies. - Siong, Hook Law (Taylor & Francis, 2009)
This paper examines the impact of trade openness and capital flows on financial development in developing countries using a dynamic panel GMM estimation technique. The empirical results reveal that trade openness and capital flows are statistically significant determinants of financial development. Simultaneous opening of both the trade and capital accounts also appear to have positive impacts on financial development. The evidence also suggests that openness leads to improved financial development through institutional quality and competition channels. However, the institutional channel outperforms competition in ensuring the positive effects of openness on financial market depth in developing countries.